Vegetation, pH and Water Content as Main Factors for Shaping Fungal Richness, Community Composition and Functional Guilds Distribution in Soils of Western Greenland - Canini, Fabiana; Zucconi, Laura; Pacelli, Claudia; Selbmann, Laura; Onofri, Silvano; Geml, József (Frontiers in Microbiology, 2019)
Fungi are the most abundant and one of the most diverse components of arctic soil ecosystems, where they are fundamental drivers of plant nutrient acquisition and recycling. Nevertheless, few studies have focused on the factors driving the diversity and functionality of fungal communities associated with these ecosystems, especially in the scope of global warming that is particularly affecting Greenland and is leading to shrub expansion, with expected profound changes of soil microbial communities. We used soil DNA metabarcoding to compare taxonomic and functional composition of fungal communities in three habitats (bare ground, biological soil crusts and vascular vegetation coverage) in West Greenland. Fungal richness increased with the increasing complexity of the coverage, but bare grounds and biological soil crusts samples showed the highest number of specific OTUs. Differences in both fungal community composition and distribution of functional guilds identified were correlated with edaphic factors (mainly pH and water content), in turn connected with the different type of coverage. These results suggest also possible losses of diversity connected to the expansion of vascular vegetation and possible interactions among the members of different functional guilds, likely due to the nutrient limitation, with potential effects on elements recycling.